Transition in the ages at key reproductive events and its determinants in India: evidence from NFHS 1992-93 to 2019-21 - Mayank Singh; Chander Shekhar; Jagriti Gupta (BMC, 2023)
Abstract Introduction Reproductive health events have changed fertility and family planning needs, depicting the changing life patterns of women and the population to which they belong. Understanding the pattern at which these events occur helps in understanding the fertility pattern, family formation and the idea about health essential needs for women. This paper attempts to see the variation in reproductive events (first cohabitation, first sex and first birth) over three decades and also to see potential contributing factors among the reproductive age group of women using secondary data from Data Source: All rounds of the National Family Health Survey (1992-93 to 2019-2021) have been utilized. Methods and Results Cox Proportional Hazard Model illustrates that all regions have initiated their first birth later than women who belong to the east region similar pattern has been obtained for first cohabitation and first sex except for the central region. Multiple Classification Analysis (MCA) depicts the increasing pattern in the predicted mean age at first cohabitation, sex and birth for all demographic characteristics; the highest increment was found in SC women, Uneducated women and Muslim women. Kaplan Meier Curve demonstrates that women with no education, primary or secondary education are shifting towards higher educated women. Most importantly, the results of the multivariate decomposition analysis (MDA) revealed that education played the largest contribution among the compositional factors in the overall increase in mean ages at key reproductive events. Conclusions Though reproductive health has long been essential in women's lives, they are still very confined to specific domains. Over time the government has formulated several proper legislative measures relating to various domains of reproductive events. However, given that the large size and heterogeneity in social and cultural norms result in changing ideas and choices regarding the initiation of reproductive events, national policy formulation needs to be improved or amended.